The Role of Psychological Capital to Job Performance with Work Engagement as Mediator of Employee - Zamralita Zamralita (Universitas Ahmad Dahlan, 2024)
A democratic state is obliged to ensure the fulfilment of the rights of its people, including the right to access quality public services. The quality and effectiveness of public services in Indonesia are currently facing significant challenges, as evidenced by a decline in the standard of service provision. This study emphasises the significance of psychological capital in enhancing job performance, with work engagement as a mediating factor. This study used quantitative methods and data collection techniques through convenience sampling, with a total of 317 participants. The instruments are used in this study for the measurement of variables are the Individual Work Performance Questionnaire, the Psychological Capital Questionnaire and the Utrecht Work Engagement Scale. The results showed that psychological capital can predict job performance, psychological capital can predict work engagement, and work engagement can predict job performance. Additionally, this study proved that work engagement functions as a mediator between psychological capital and job performance. By enhancing psychological capital and work engagement, the quality of public services can be enhanced, which will have a beneficial impact on public trust and public welfare.